New country records with nomenclatural and distributional updates in Artemisia (Asteraceae) of Tunisia and notes on related North African endemic taxa - Mokni, Ridha El; Domina, Gianniantonio (Phytotaxa, 2026)
Two taxa of Artemisia subg. Artemisia (A. kabylica and A. judaica subsp. sahariensis) are reported as new to Tunisia. In addition, new records are presented for A. atlantica. Their descriptions and notes on their habitat, ecology, and distribution in Tunisia together with their regional conservation status are given. Original photographs along with an analytical key to taxa of A. subg. Artemisia endemic to North Africa are presented. The names Artemisia judaica var. sahariensis L.Chevall. and A. atlantica Coss. & Durieu are lectotypified.